The Philosophy of Kuda Leupas ti Gedogan: An Analysis of the Religious Deviation of Students in Ormas-Based Islamic Boarding Schools in Garut Regency - Tohari, Heri Mohamad; Layinah, Leni; Resiana, Gina; Qoyyimah, A. Sofi; Ahmad, Soni (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This study aims to determine the religious deviation that occurs in several Islamic boarding schools under the auspices of Islamic community organizations (Ormas) in Garut Regency. The focus of the study is directed at the forms of behavioral deviations of students in four Islamic boarding schools affiliated with organizations: Nahdlatul Ulama (NU), Muhammadiyah, Persatuan Islam (Persis), and Syarikat Islam (SI). The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that in the four Islamic boarding schools, similar forms of religious deviation were found, which the local community calls "horse loose from gedogan", namely deviant behavior that shows disobedience to the values of the Islamic boarding school. However, each Islamic boarding school has its own strategy in overcoming this deviant behavior. The conclusion of this study shows that religious deviation is influenced by internal factors as well as external factors in the form of a less conducive and uneducational social environment, so that it becomes a challenge in achieving the goals of Islamic boarding school education.